2021
DOI: 10.1093/bjsopen/zrab096
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nutritional status and body composition on postoperative outcomes after pelvic exenteration for locally advanced and locally recurrent rectal cancer

Abstract: Background Pelvic exenteration for locally advanced rectal cancer (LARC) and locally recurrent (LRRC) rectal cancer provides radical resection and local control, but is associated with considerable morbidity. The aim of this study was to determine risk factors, including nutritional status and body composition, for postoperative morbidity and survival after pelvic exenteration in patients with LARC or LRRC. Methods Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…We found that patients undergoing PE who were sarcopenic did not diverge significantly from those who were non-sarcopenic in local recurrence, distant recurrence, DFS, and OS rates. In coherence with our results, Rees et al showed body composition variables had no effect on overall survival in their multivariable analysis [ 25 ]. Interestingly, a small Austrian study reported that preoperative low muscle attenuation, an established factor for muscle depletion, was associated with shorter survival in patients with recurrent gynaecological malignancies treated with PE [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that patients undergoing PE who were sarcopenic did not diverge significantly from those who were non-sarcopenic in local recurrence, distant recurrence, DFS, and OS rates. In coherence with our results, Rees et al showed body composition variables had no effect on overall survival in their multivariable analysis [ 25 ]. Interestingly, a small Austrian study reported that preoperative low muscle attenuation, an established factor for muscle depletion, was associated with shorter survival in patients with recurrent gynaecological malignancies treated with PE [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…They concluded that preoperative sarcopenia measured radiologically was not sensitive enough to predict postoperative complications and outcomes in oncologic patients following PE surgery. Furthermore, Rees et al investigated the impact of body composition on postoperative outcomes after PE surgery in 227 patients with locally advanced and locally recurrent rectal cancer [ 25 ]. Of the body composition variables investigated, patients with low skeletal muscle mass, muscle wasting, and low skeletal muscle density (SMD) were not associated with major postoperative complications (CD grade ≥ 3).…”
Section: Discussionmentioning
confidence: 99%
“…While the number of QoL studies has increased significantly over the past 10 years in the surgical literature, there remain relatively few studies that have investigated QoL of patients with LARC and LRRC either collectively or separately. 3,6,7 Additionally, no studies have directly compared QoL outcomes between the 2 diseases. [4][5][6]8 As far as the authors are aware, there has only been 1 study that compared surgical outcomes between LARC and LRRC after PE.…”
Section: Principales Medidas De Resultadomentioning
confidence: 99%
“…The PelvEx Collaborative group published a multicenter study, which investigated the trend of operative and surgical outcomes of the 2. 7 They reported a flap reconstruction rate of 29.4% for LARC and 24.4% for LRRC between 2014 to mid-2015. In this study, the flap reconstruction rate for LARC was lower than it was in their finding, whereas it was similar for patients with LRRC.…”
Section: Discussionmentioning
confidence: 98%
“…Malnutrition occurs frequently in patients before pancreatic surgery, and its prevalence fluctuates from 36 to 88% according to different diagnostic criteria [4]. As an intervenable factor, nutritional status has been used to explore the effects on postoperative short-term and long-term outcomes in patients who underwent major oncologic surgery [5][6][7][8][9][10][11][12][13][14][15][16]. Despite validated nutritional assessment tools are various (such as weight loss [17], muscle mass [18], Mini Nutrition Assessment (MNA) scores [19], and subjective global assessment (SGA) scores [20]), body mass index (BMI) [21] and albumin [22] are still the most widely utilized due to their easy availability.…”
Section: Introductionmentioning
confidence: 99%